Diversity and biomass of tree species in Tambrauw, West Papua, Indonesia - IYAN ROBIANSYAH (Society for Indonesian Biodiversity, 2018)
Robiansyah I. 2018. Diversity and biomass of tree species in Tambrauw, West Papua, Indonesia. Biodiversitas 19: 377-386. In spite of its high diversity and endemism, New Guinea is still one of the least explored regions on the globe. Flora information for the island as a whole is low compared to other areas in Malesia, and for Indonesian Province of Papua and West Papua it is much lower than for Papua New Guinea. To add more information and data on the flora of the West Papua Province, a vegetation analysis was conducted in Fef (442-509 m) and Bamusbama (757-914 m) Subdistricts, Tambrauw District, West Papua, Indonesia. Six and four plots of 30x30 m were placed in Fef and Bamusbama, respectively, to assess and compare the diversity and biomass of trees with diameter at breast height ? 10 cm. A total of 457 stems and ca. 86 tree species were identified. Fef accommodated higher species number (70) than Bamusbama (42). Meliaceae and Myrtaceae were the most important families in Fef and Bamusbama, respectively, while Castanopsis acuminatissima was the most important species in both subdistricts.The species diversity, richness, and evenness in Fef was higher than in Bamusbama. For tree biomass, the estimated value in Bamusbama (383.8 ton/ha) was much higher than in Fef (224.7 ton/ha). The results of the present study may serve as a baseline information for sustainable forest management and conservation of the region.